2023
DOI: 10.2106/jbjs.oa.22.00125
|View full text |Cite
|
Sign up to set email alerts
|

Predeposited Autologous Blood Transfusion in Single-Anesthetic Bilateral Total Knee Arthroplasty with Modern Blood Conservation Strategy

Abstract: Background:This study was performed to examine the hypothesis that the rate of allogeneic blood transfusion in patients who did not predeposit an autologous blood transfusion before single-anesthetic bilateral total knee arthroplasty (TKA) would be noninferior to that in patients who did predeposit blood.Methods:We assessed the number of allogeneic transfusions required in 338 patients undergoing single-anesthetic bilateral TKA with a preoperative hemoglobin level of ≥11.0 g/dL. All TKAs were performed by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Concerning the use of ABT, it reportedly decreased transfusion rates compared with closed suction drainage but showed no difference in terms of postoperative Hb drop [ 27 , 28 ]. Although Tsukada et al stated that there was no need for ABT even in single-anesthetic bilateral TKA [ 29 ], Tomura et al reported that the perioperative Hb change was relatively small with ABT and the transfusion rate was 1%, suggesting that the cost-effectiveness of this method is debatable but nevertheless beneficial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the use of ABT, it reportedly decreased transfusion rates compared with closed suction drainage but showed no difference in terms of postoperative Hb drop [ 27 , 28 ]. Although Tsukada et al stated that there was no need for ABT even in single-anesthetic bilateral TKA [ 29 ], Tomura et al reported that the perioperative Hb change was relatively small with ABT and the transfusion rate was 1%, suggesting that the cost-effectiveness of this method is debatable but nevertheless beneficial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%